Claroideoglomus etunicatum and Bacillus thuringiensis Affect the Growth of the Invasive Plant Ageratina adenophora and Its Defense Against the Specialist Herbivore Procecidochares utilis - Ewei Du; Pengcun Li; Wenyuan Zhao; Rongchao Luo; Yaping Chen; Minghong Lu; Zhongxiang Sun; Furong Gui (Microorganisms)
Exotic plants can selectively recruit beneficial microorganisms, such as arbuscular mycorrhizal fungi (AMFs) and Bacillus spp., during their invasion process to enhance growth and competitiveness by improving nutrient absorption and strengthening defense capabilities against herbivores. However, research in the context of invasive plants remains limited. In this study, a greenhouse pot experiment was conducted to examine the effects of different treatments on the growth and defense of Ageratina adenophora. The treatments included no inoculation, inoculation with Bacillus thuringiensis (BT), inoculation with arbuscular mycorrhizal fungus (Claroideoglomus etunicatum, CE), dual inoculation with BT and CE (BT + CE), and the presence or absence of Procecidochares utilis. The results showed that both CE and BT + CE significantly enhanced nutrient concentration and promoted the growth of A. adenophora. The aboveground biomass increased by 35.48 and 53.38% under non-parasitism and by 68.03% and 103.72% under the parasitism of P. utilis for these two treatments, respectively. In comparison to the control P. utilis-parasitized A. adenophora, the BT, CE, and BT + CE treatments significantly increased protective enzyme activity, jasmonic acid concentration, and secondary metabolites. Our study indicates that the recruitment of B. thuringiensis in the rhizosphere of A. adenophora can enhance its defense ability, while C. etunicatum improved both growth and defense ability. The interaction effects of these two microorganisms enhances the regulation of growth and defense ability of A. adenophora against P. utilis parasitism, providing insights into the feedback effects of beneficial microorganisms on the interactions between invasive plants and biological control.